Mean Platelet Volume and Immature Platelet Fraction as Biomarkers in Differentiating Early-Onset and Late-Onset Neonatal Sepsis - Rahmi Dina Indra; Rikarni; Desiekawati; Zelly Dia Rofinda; Dwi Yulia; Elfira Yusri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Neonatal sepsis is a significant contributor to infant mortality, with millions of cases occurring globally each year. It is classified into early-onset neonatal sepsis (EONS), occurring within the first 72 hours of life, and late-onset neonatal sepsis (LONS), occurring after 72 hours. Thrombocytopenia is a common finding in neonatal sepsis, and the degree of thrombocytopenia has been associated with the severity of the disease. Mean platelet volume (MPV) and immature platelet fraction (IPF) are markers of platelet size and immaturity, respectively, and may provide insights into the pathophysiology of sepsis and aid in its diagnosis. Methods: This cross-sectional analytical study was conducted at Dr. M. Djamil General Hospital in Padang, Indonesia, from June to September 2024. The study included 41 neonates diagnosed with sepsis. Complete blood counts were performed using an automated hematology analyzer to determine MPV, IPF, and platelet count. Neonatal sepsis was classified as EONS (within the first 7 days of life) or LONS (from day 8 to 28). Data were analyzed using descriptive statistics and the unpaired t-test. Results: The mean age of the neonates was 11.6 days. There were 19 neonates with EONS and 22 with LONS. The mean MPV was significantly higher in the LONS group (11.7 fL) compared to the EONS group (10.2 fL) (p=0.001). Similarly, the mean IPF was significantly higher in the LONS group (10.9%) compared to the EONS group (7.7%) (p=0.001). There was no significant difference in platelet count between the two groups. Conclusion: MPV and IPF were significantly higher in neonates with LONS compared to those with EONS, suggesting that these parameters may be useful biomarkers for differentiating between the two conditions. Further research with a larger sample size and longitudinal follow-up is needed to confirm these findings and to assess the potential clinical utility of MPV and IPF in the management of neonatal sepsis.